Commodity Markets Outlook, July 2016 : From Energy Prices to Food Prices - World Bank Group (World Bank, Washington, DC, 2016)
Most commodity price indexes rebounded in the second quarter of 2016, continuing their upward climb from January lows on improved market sentiment and tapering supplies. Oil prices jumped by more than a third due to supply outages and strong demand. Given this rebound and expected reduction in inventories during the second half of the year, the crude oil price forecast for 2016 is being raised to 43 dollars per barrel (bbl) from 41 dollars per bbl in the April assessment, still a 15 percent drop from 2015. Metals prices are projected to decline 11 percent in 2016, a slightly larger drop than anticipated in April, mainly driven by an ongoing surplus in the copper market. Agricultural prices for 2016 have been revised slightly upwards due to weather patterns in South America, but are still expected to register a marginal decline from last year. A large upward revision for precious metal prices of more than 8 percentage points versus the April assessment reflects the increased demand for safe haven assets. For 2017, a modest recovery is projected for most commodities as demand strengthens and supply tightens. This issue of the Commodity Markets Outlook examines the implications of low energy prices for food prices. It finds that, given the energy-intensive nature of agriculture, high energy prices were an important driver of the post-2006 surge in agricultural prices. Over 2011-2016, lower energy prices are estimated to account for up to one-third of the projected 32 percent decline in prices of grains and soybeans.